"We are a collective, a lot of us together, standing up": South African black lesbian women's activism against discourses of blackwashing homophobia. Issue 2 (3rd April 2019) - Pinheiro, Gabriela; Harvey, Clare
Abstract: Research centring South African black lesbian women's identities has increased significantly in recent years. However, a politics of visibility (in academic and public spaces) has not secured equal status and human rights for many of these women. Instead, dominant discourses of blackwashing homophobia (re)produce colonial strategies of othering, associating their identities with violence, fear, shame and victimhood. Black lesbian women are often constructed as inevitable targets of special crimes – particularly that of 'corrective rape' in township settings (in the case of South Africa). This repeated, negative stereotype conceals the effects of historical and contemporary inequalities that constrain the constitutional protection and social sanctioning of black, queer identities. An increasingly relevant, but under-examined area of study is the potential for collective political action to disrupt reductionist discourses, recognising these women's identities as whole, plural, fluid, complex and contradictory. This article thus focalises one exemplar of such resistance, using a feminist, intersectional methodological framework to explore secondary, textual data. The findings contribute to a growing body of research that foregrounds intersectionality theory as a valuable lens through which contemporary South African identities can be viewed. Counter-discourses that challenge blackwashing strategies are also offered. The findings allude specifically to the significance of black lesbian women's community-level mobilisation against gender-based violence, and its intersections with racial and sexual inequalities. Where blackwashing discourses tend to essentialise and divide these identities into parts, findings suggest that for some black lesbian women, racial, gendered and sexual identities are indivisible: connected particularly to joy, solidarity, pleasure, power, resilience and strength.